A Multilevel Analysis of Real-World Variations in Oral Anticoagulation Initiation for Atrial Fibrillation in Valencia, a European Region - García-Sempere, Aníbal; Bejarano-Quisoboni, Daniel; Librero, Julián; Rodríguez-Bernal, Clara L.; Peiró, Salvador; Sanfélix-Gimeno, Gabriel (Frontiers in Pharmacology, 2017)
Introduction. Beyond clinical trials, clinical practice guidelines and administrative regulation, treatment decision-making can be influenced by individual and contextual factors. Our goal was to describe variations in the patterns of initiation of anticoagulation therapy in patients with atrial fibrillation by Health Areas (HA) in the region of Valencia in Spain and to quantify the influence of the HAs on variations in treatment choice. Methods. We conducted a population-based retrospective cohort study of all atrial fibrillatrion patients who started treatment with oral anticoagulants between November 2011 and February 2014 in each of the region’s 24 HAs. We described patient and utilisation characteristics per HA and initiation patterns over time, and we identified contextual and individual factors associated with differences in initiation patterns. Results. 21.879 patients initiated treatment with an oral anticoagulant in the 24 HAs. Initiation with direct oral anticoagulants (DOAC) in the first year was 14,6%. In November 2013 the ratio was 25,4%, with HA ratios ranging from 3,8% to 57,1%. DOAC-initiating patients had less comorbidity but were more likely to present episodes of previous ischemic stroke, hemorrhagic stroke or TIA when compared with patients initiating with VKA treatment. Variability among HAs was statistically significant, with the majority of HAs ranking above or below the regional initiation average (ICC≈8%). Conclusion. There was high variability in the percentage of DOAC initiation and in the choice of DOAC among HAs. Interventions aimed to improve DOAC initiation decision-making and to reduce variations should take into account the Health Area component.